2012
DOI: 10.1242/jeb.062034
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between plasma oxidative status, cortisol and coping styles in wild alpine marmots, Marmota marmota

Abstract: SUMMARYVariation in how individuals cope behaviourally and physiologically with stressors is widespread and can have a significant impact on life-history traits and fitness. Individual coping styles are characterised by differential behavioural and adrenocortical reactivity to various challenges. As stress hormones can affect the production of reactive chemical species and the antioxidant status, individuals with different coping styles may differ also in oxidative status. Field studies on wild mammalian popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 78 publications
2
39
3
Order By: Relevance
“…16 Individual characteristics are also expected to influence territory size and shape (Boyer et al 2010). In two recent works on copying styles (see Koolhaas et al 1999) we showed that Alpine marmots present consistently repeatable behavioural traits (Costantini et al 2012, Ferrari et al 2013. Future research should investigate how space use could be affected by individual differences accounting for both the environment resource availability and density of the population (Dingemanse et al 2004).…”
Section: Discussionmentioning
confidence: 86%
“…16 Individual characteristics are also expected to influence territory size and shape (Boyer et al 2010). In two recent works on copying styles (see Koolhaas et al 1999) we showed that Alpine marmots present consistently repeatable behavioural traits (Costantini et al 2012, Ferrari et al 2013. Future research should investigate how space use could be affected by individual differences accounting for both the environment resource availability and density of the population (Dingemanse et al 2004).…”
Section: Discussionmentioning
confidence: 86%
“…Each hypothesized DAG can be defined by the implied conditional independencies owing to the assumed causal links among the variables, which can then be statistically tested by translating them into structural equations [21,24]. While confirmatory path analysis and structural equation models have widely been applied in general ecology [25,26], ecophysiology [27,28] and evolutionary biology [29], we are not aware of any study using them in the field of molecular ecology.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be caused by a week of social defeat in rats (Avitsur, Stark, Dhabhar, Padgett, & Sheridan, 2002). In wild alpine marmots, Marmota marmota, and eastern chipmunks, Tamias striatus, glucocorticoid measures positively correlate with open-field behaviour (Costantini et al, 2012;Ferrari et al, 2013;Montiglio, Garant, Pelletier, & R eale, 2012). These studies demonstrate that the stress response plays a key role in both behavioural and immune variation, suggesting that glucocorticoids can affect the relationship between behaviour and immunity.…”
mentioning
confidence: 75%